Duty Free: Turning the Criminological Spotlight on Special Economic Zones. (10th March 2022) - Hall, Alexandra; Antonopoulos, Georgios A; Atkinson, Rowland; Wyatt, Tanya
Abstract: Spatially designated economic zones render countries vulnerable to crime and harm, while simultaneously diffusing and escalating these problems across the globe. Yet, criminological analysis of special economic zones (SEZs) and similar areas remains limited. This article analyses the kinds of criminality and harm attached to such fiscal and commodity enclaves. Our analysis begins with the history of SEZs. We then offer a typology of related harms: 1. illicit trade; 2. the protection of wealth holdings; and 3. environmental harm. Our closing theoretical discussion suggests how the expansion of economic strategies involving SEZs is generative of new and complex forms of harm and crime embedded in the spatial architecture of the global economy.